2023
DOI: 10.3390/ijms24054571
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Circular RNAs in Cardiovascular Diseases

Abstract: Cardiovascular disease (CVD) remains the leading cause of mortality globally. Circular RNAs (circRNAs) have attracted extensive attention for their roles in the physiological and pathological processes of various cardiovascular diseases (CVDs). In this review, we briefly describe the current understanding of circRNA biogenesis and functions and summarize recent significant findings regarding the roles of circRNAs in CVDs. These results provide a new theoretical basis for diagnosing and treating CVDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 132 publications
0
14
0
Order By: Relevance
“…The unique attribute of circRNAs is a continuous closed-loop structure, allowing for circulatory stability with resistance to nucleases that degrade linear RNAs [ 97 , 98 ]. CircRNAs function as sponges to miRNAs, bind proteins directly, and like lncRNAs, can encode their own proteins [ 99 ]. CircRNAs can contain 200–2000 base pairs, giving each a massive array of potential regulatory functions with many potential targets and binding sites [ 100 , 101 ].…”
Section: Circular Rnas In Cardiac Disease and Fibrosismentioning
confidence: 99%
“…The unique attribute of circRNAs is a continuous closed-loop structure, allowing for circulatory stability with resistance to nucleases that degrade linear RNAs [ 97 , 98 ]. CircRNAs function as sponges to miRNAs, bind proteins directly, and like lncRNAs, can encode their own proteins [ 99 ]. CircRNAs can contain 200–2000 base pairs, giving each a massive array of potential regulatory functions with many potential targets and binding sites [ 100 , 101 ].…”
Section: Circular Rnas In Cardiac Disease and Fibrosismentioning
confidence: 99%
“…A recent study highlighted the significant role of circRNAs in the development and progression of AF, identifying specific circRNAs that are differentially expressed in both the left and right atrial appendages of AF patients ( Table 7 ). The research suggested that circRNAs, particularly hsa_circ_0003965, may be involved in AF through a unique regulatory mechanism potentially associated with the glucagon signaling pathway [ 80 ].…”
Section: Arrhythmiamentioning
confidence: 99%
“…These substances have the potential to modify the regular operation of the cardiac system and play a role in the advancement of cardiomyopathies. Hence, gaining a comprehensive understanding of the involvement of ncRNAs in cardiomyopathies has the potential to offer novel perspectives on the molecular mechanisms that underlie these pathological conditions, and consequently, facilitate the exploration of innovative therapeutic approaches 102 …”
Section: Noncoding Rnas In Cardiomyopathiesmentioning
confidence: 99%
“…Hence, gaining a comprehensive understanding of the involvement of ncRNAs in cardiomyopathies has the potential to offer novel perspectives on the molecular mechanisms that underlie these pathological conditions, and consequently, facilitate the exploration of innovative therapeutic approaches. 102…”
Section: Dysregulation Of Noncoding Rnas In Cardiomyopathiesmentioning
confidence: 99%